Empties in translation of Blanka Bartošová and Kathleen Hayes - Nováková, Michala (Univerzita Pardubice, 2009)
This bachelor paper deals with the comparative study of the Czech and the English versions of the bittersweet comedy Empties with the main emphasis placed on a degree to which the translated subtitles can be closer to either the Czech or the English viewers. The analysis is focused mainly on proper names, which can, after the external linguistic, cultural and other pragmatic factors are taken into account, signal in the rendered text important pieces of information about its origin. The theoretical part of the paper defines the Svěráks' film style as well as the basic methods and principles of translation concentrated mainly on subtitling and transferring culture-bound expressions and proper names. The practical part carries out the qualitative and quantitative analysis of the techniques making the subtitles familiar to either the source or the target language culture.
Keywords: Translation; comparison of originals and translations; Empties; Zdeněk and Jan Svěráks; proper names; překladatelství; porovnání překladů a originálů; Vratné láhve; Zdeněk a Jan Svěrákové; vlastní jména